Revision of Land Use Law: what consequences for land rent? - Emília Malcata Rebelo (2009)
In this article some considerations are made concerning the revision of the land use law (that is currently being undertaken) , in line with its articulation with the basis of the Policy of Territorial Ordinance, and with the juridical regime of territorial management tools, in order to point out some key issues in territorial planning goals concerning: the need to provide land for the different kinds of uses at acceptable prices (ensuring the right of urban property), the encouragement of the private initiative of promoters, builders and sellers, and the monitoring and control of surplus-values generated by planning decisions (thus preventing speculative processes). Within this scope, an analysis of the concept of land rent is carried on, and the consequences of the different kinds of public interventions on property values are analysed, in terms of the surplus-values they generate. Next is presented a methodology to compute land rent and surplus values that is applied, as a case study, to the office market of Oporto city (Portugal). This methodology considers the different variables that intervene in land and real estate price formation, the inter-relations between property values, the licensed land uses, and the behaviours of the different agents involved in property markets. Some concluding reflections are made on how the revision of the land use law can lead to the appropriate provision of land, considering its social function, the control of its price levels, and the stimulus to territorial development within an increasingly uncertain environment.